2018
DOI: 10.24247/ijdrddec20181
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Activity of SGLT – 2 Inhibitors in Albinomice, an Experimental Study

Abstract: ObjectiveTo evaluate the antidepressant activity of SGLT-2 inhibitors in mice. MethodsSixty adult Swiss albino mice weighing 25-30 grams were selected. Thirty were allocated to forced swim test and thirty to tail suspension test models. In each model, there were 4 groups. The control group received vehicle (10 ml/kg, p. o) as standard, Imipramine (10 mg/kg, p. o) and the two test groups received dapagliflozin and capagliflozon respectively1hour prior to the acute study. In chronic study, the drugs were given o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…While early case reports suggested a potential association between incretin-based therapies and depression [11,12], recent cohort studies have found that DPP4I use is generally associated with a reduced risk of depression [13][14][15][16]. This is confirmed by clinical findings that DPP4 enzymatic activity is increased in patients with depressive symptoms [17] as well as pre-clinical findings in rodent model that DPP4I use produces antidepressant effects [18,19]. By contrast, there is limited data available to assess the anti-depressant effects of SGLT2I.…”
Section: Introductionmentioning
confidence: 83%
“…While early case reports suggested a potential association between incretin-based therapies and depression [11,12], recent cohort studies have found that DPP4I use is generally associated with a reduced risk of depression [13][14][15][16]. This is confirmed by clinical findings that DPP4 enzymatic activity is increased in patients with depressive symptoms [17] as well as pre-clinical findings in rodent model that DPP4I use produces antidepressant effects [18,19]. By contrast, there is limited data available to assess the anti-depressant effects of SGLT2I.…”
Section: Introductionmentioning
confidence: 83%